Spatial and seasonal variability of excess dinitrogen gas in the Baltic Sea - Pratha Sivasamy; Magdalena Diak; Aleksandra Winogradow; Hermann W. Bange; Marta Borecka; Przemysław Makuch; Katarzyna Koziorowska-Makuch; Karol Kuliński; Anna Mackiewicz; Beata Szymczycha (Frontiers in Marine Science)
To determine the excess of dissolved dinitrogen gas (ΔN2 > 0 indicates the loss of bioavailable dissolved nitrogen) in the water column of the Baltic Proper, we measured N2/Ar ratios below the halocline at 19 stations during different seasons between 2017 and 2021. ΔN2 concentrations below the halocline ranged from 1.0 to 32.6 µmol L-1 for all seasons and sites. A significant spatial difference in ΔN2 (p = 0.0001) was observed, with the highest values found in the Gotland Deep. The seasonal changes in ΔN2 were statistically significant (p = 0.005) with the highest concentrations observed in winter. To our knowledge, this is the first study showing the variability of ΔN2 on a large scale in the Baltic Proper. Our findings suggest that the cumulative loss of bioavailable nitrogen via denitrification and anammox is an important mechanism in the Baltic Sea nitrogen cycle. The accumulated signal of N2 production is, however, not uniform across the Baltic Proper, exhibiting significant seasonal and spatial variabilities. This calls for future, investigations on a broad spatial scale and a seasonal resolution which focus on denitrification and anammox rates in the water column, by utilizing a consistent methodological approach. It is essential to ensure an accurate representation of the nitrogen loss, which in turn is important for managing eutrophication and maintaining a good environmental status in the Baltic Sea.